Regime Stability and the Persistence of Traditional Practices - Poyker, Michael (The Review of Economics and Statistics, 2023)
Abstract I examine why the harmful tradition of female genital mutilation (FGM) persists in certain countries but in others it has been eradicated. People are more willing to abandon their traditions if they are confident that the government is durable enough to set up long-term replacements for them. Using a country-ethnicity panel data set spanning 23 countries from 1970 to 2013 and artificial partition of African ethnic groups by national borders, I show that a one-standard-deviation larger increase in political regime durability leads to a 0.1-standard-deviation larger decline in the share of newly circumcised women, conditional on the presence of an anti-FGM government policy.